2009
DOI: 10.1002/aic.11848
|View full text |Cite
|
Sign up to set email alerts
|

Application of the distributed activation energy model to biomass and biomass constituents devolatilization

Abstract: In this study, an investigation about the thermal behavior of four different woods was carried out. The distributed activation energy model was applied to study the effect of heating rate on the reaction of single solids. Results obtained were used in the curve prediction of fraction of mass remaining and rate of mass loss vs. temperature at more realistic heating rates. The possible calculation of biomass samples behavior in pyrolysis conditions as the summation of their constituents, lignin, cellulose, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 23 publications
7
22
0
Order By: Relevance
“…The devolatiliza tion of biomass occurred at a lower temperature, between 100 and 600°C, while operating with sewage sludge, the temperature must be as high as 1000°C to reach a high conversion rate [29]. The tem peratures at which pine conversion occurs are in good agreement to those obtained by Biagini et al [27] and Navarro et al [28], and they are also similar to those obtained by Sonobe et al [25] who analyzed the devolatilization of biomasses with a high content of cellulose.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The devolatiliza tion of biomass occurred at a lower temperature, between 100 and 600°C, while operating with sewage sludge, the temperature must be as high as 1000°C to reach a high conversion rate [29]. The tem peratures at which pine conversion occurs are in good agreement to those obtained by Biagini et al [27] and Navarro et al [28], and they are also similar to those obtained by Sonobe et al [25] who analyzed the devolatilization of biomasses with a high content of cellulose.…”
Section: Resultssupporting
confidence: 85%
“…The results of the proximate and the ultimate analyses of the pine samples are comparable to those of Biagini et al [27], Shen et al [26], and Navarro et al [28]. On the other hand, the results for the sewage sludge can be compared to those of Scott et al [29], although in this case there are higher differences due to the great heterogeneity of sewage sludge.…”
Section: Methodssupporting
confidence: 79%
“…Wood decomposition takes place mainly in three steps [21]: first lignin decomposition, which lasts until 500 ºC, followed by hemicellulose decomposition and, finally, cellulose decomposition. Tyre pyrolysis has been also described elsewhere [20,22,23] and three main steps of devolatilisation are also found: a first step of low reaction rates linked to pyrolysis of tyre rubber additives; a second step with a sharp peak related to natural rubber decomposition and finally, a third step assigned to the decomposition of synthetic rubber (styrene-butadiene rubber and butyl rubber).…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…According to Baliga et al (2003), pectin showed initial melting as early as 150ºC and a total melt by 250ºC. Meanwhile, hemicellulose started to decompose at a temperature near 450 K (Navarro et al 2009). This indicated that the peak at 189ºC may be caused by the decomposition of pectin and hemicellulose.…”
Section: Fig 1 Tg and Dtg Curves Of Tobacco Stemmentioning
confidence: 99%